Hubungan Pemberian ASI Eksklusif dengan Pertumbuhan dan Perkembangan pada Bayi Usia 7-12 Bulan di Puskesmas Susua Nias Selatan - Soriadanomo Telaumbanua; Adelina Sembiring; Lisbet Gurning; Sri Mulati Nendah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Exclusive breastfeeding plays an important role in the growth and development of infants. The World Health Organization (WHO) recommends exclusive breastfeeding for the first six months of life, followed by complementary foods (MPASI). However, many mothers do not provide exclusive breastfeeding, which can affect the growth and development of infants in old age. This study aims to analyze the relationship between exclusive breastfeeding and the growth and development of infants aged 7-12 months.This study uses a quantitative research type using Retrospective research. The design of this study was carried out with a cross-sectional approach, the sample in the study was 62 people using the Random Sampling System. The data collected in the study were primary data, namely data obtained directly from respondents. The data analysis used was Chi Square. Exclusive breastfeeding in infants aged 7-12 months is mostly given exclusive breastfeeding (56.6%), growth in infants aged 7-12 months is mostly fat (37.1%), development in infants aged 7-12 months is mostly normal (54.8%), there is a relationship between exclusive breastfeeding and growth in infants aged 7-12 months with a p-value of 0.000, there is a relationship between exclusive breastfeeding and development in infants aged 7-12 months with a p-value of 0.000. So Ho is rejected and Ha is accepted which means there is a relationship between exclusive breastfeeding and development in infants aged 7-12 months. For further researchers, it is expected to be able to conduct further research by developing other variables in order to get better results.